Scaling Up Handwashing Behavior : Findings from the Impact Evaluation Baseline Survey in Peru - Galiani, Sebastian (Washington, DC, 2014)
In response to the preventable threats posed by poor sanitation and hygiene, the Water and Sanitation Program (WSP) launched two large-scale projects, global scaling up handwashing and global scaling up rural sanitation, to improve the health and welfare outcomes for millions of poor people. Local and national governments are implementing these projects with technical support from WSP. Global scaling up handwashing aims to test whether handwashing with soap behavior can be generated and sustained among the poor and vulnerable using innovative promotional approaches. The primary objectives are to reduce the risk of diarrhea in young children and increase household productivity by stimulating and sustaining the behavior of handwashing with soap at critical times. Overall, the project aims to generate and sustain handwashing with soap practices among 5.4 million people living in Peru, Senegal, Tanzania, and Vietnam, the four countries where the project has been implemented to date. This technical paper presents the findings of the WSP impact evaluation (IE) baseline survey in Peru and is one in a series of papers presenting IE findings from surveys conducted in each project country.